Rekonstruksi Epistemologi Pendidikan Agama Islam: (Kajian Pemikiran Hasan Hanafi Teosentris-Antroposentris) - Saehu Abas; Hajjin Mabrur (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
This research discusses the reconstruction of epistemology of Islamic religious education; Hasan Hanafi's theocentric-anthropocentric thought study. His study was motivated by the epistemology of Islamic religious education which has been impressed still dominated by doctrinal education rather than education, tends to be textual rather than contextual and more densely theoretical than practical. This research aims to conduct an in-depth analysis and research study of the epistemological construction of Islamic religious education that has been formulated, and will further be studied and analyzed using the paradigm of Hasan Hanafi theory through the Theocentric-Anthropocentric theory. This research uses a type of qualitative research with an approach using library research methods. In accordance with the topic discussed, the researcher classified the data source into a primary data source taken from one of Hasan Hanafi's works, The Dirasah Islamiyah translated by Miftah Faqih into three volumes of books; (1) From Static Theology to Anarchists. (2) From Rationalism to Empiricism. (3) From Theocentric to Anthropocentric, and secondary data sources as advocates that have relevance to the discussion, both from books, thesis, thesis, desertation, journals, articles, and so on. Data collection techniques use observation techniques as well as documentation, and finally for data analysis techniques using content analysis techniques, inductive analysis, deductive analysis, descriptive analysis and interpretive analysis. The results showed that with the shift in the epistemological concept of Islamic religious education towards the theocentric-anthropocetic theory of Hasan Hanafi, it can lead to the creation of learners who reflect the values and insights of social-democratic knowledge as manifestations of the teachings of hablumminannas. Insight into knowledge of leadership, independence, and active awareness of his existence as a manifestation of human responsibility as khalifah fil ard. Insight into knowledge of the spirit of the progressive, productive soul of creative and innovative results as aifestasi of the value of the teachings of the sholikh likulli zaman wa makan. Insight into knowledge of unity in diversity as manifestation of the Islamic teachings of rahmatan lil ‘alamin. As well as the presence of the soul that has a culture of dialogue as from the time of the Prophet until the time of tabi'in is known as the mujadalah tradition. Abstrak Penelitian ini membahas tentang rekonstruksi epistemologi pendidikan agama Islam; kajian pemikiran Hasan Hanafi teosentris-antroposentris. Kajiannya dilatarbelakangi oleh epistemologi pendidikan agama Islam yang selama ini terkesan masih didominasi oleh pendidikan doktrinasi dari pada edukasi, cenderung tekstual dari pada kontekstual dan lebih padat teoritis dari pada praktis. Penelitian ini bertujuan untuk melakukan kajian analisis dan penelitian mendalam terhadap konstruksi epistemologi pendidikan agama Islam yang selama ini dirumuskan, dan selanjutnya akan dikaji dan dianalisis menggunakan paradigma berfirikir Hasan Hanafi melalui teori Teosentris-Antroposentris. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan menggunakan metode penelitian kepustakaan (library research). Sesuai dengan topik yang dibahas, maka peneliti mengklasifikasi sumber data menjadi sumber data primer yang diambil dari salah satu karya Hasan Hanafi, Dirasah Islamiyah yang diterjemahkan oleh Miftah Faqih kedalam tiga jilid buku; (1) Dari Teologis Statis ke Anarkis. (2) Dari Rasionalisme ke Empirisme. (3) Dari Teosentris Menuju Antroposentris, dan sumber data sekunder sebagai penujang yang memiliki relevansi terhadap pembahasan, baik dari buku, skripsi, tesis, desertasi, jurnal, artikel, dan sebagainya. Teknik pengumpulan data menggunakan teknik observasi serta dokumentasi, dan terakhir untuk teknik analisis data menggunakan teknik analisis konten, analisis induktif, analisis deduktif, analisis deskriptif dan analisis interpretatif. Hasil penelitian menunjukan bahwa dengan adanya pergeseran konsep epistemologi pendidikan agama Islam menuju teori teosentris-antropoosetris Hasan Hanafi, maka dapat mengarahkan kepada pencipataan peserta didik yang mencerminkan nilai dan wawasan pengetahuan sosial-demokratis sebagaimana manifestasi dari ajaran hablumminannas. Wawasan pengetahuan tentang kepemimpinan, kemandirian, serta kesadaran aktif akan eksistensi dirinya sebagaimana manifestasi dari tanggung jawab manusia sebagai khalifah fil ard. Wawasan pengetahuan tentang semangat jiwa progresif, produktif dari hasil kreatif dan inovatif sebagai menifestasi dari nilai ajaran sholikh likulli zaman wa makan. Wawasan pengetahuan tentang persatuan dalam keberagaman sebagaimana manifestasi dari ajaran Islam rahmatan lil 'alamin. Serta kehadiran jiwa yang memiliki budaya dialog sebagaimana sejak masa Nabi hingga masa tabi’in dikenal dengan tradisi mujadalah.